Synthesis, Structural Aspects and Catalytic Performance of a Tetrahedral Cobalt Phosphonate Framework. Issue 28 (30th July 2013) - Sen, Rupam; Saha, Debraj; Mal, Dasarath; Brandão, Paula; Rogez, Guillaume; Lin, Zhi
Abstract: A new phosphonate‐based metal organic framework has been synthesized. The structure determined by X‐ray crystallography reveals that it has an interesting 8‐ring channel 3D structure having the Co2 ‐dimers as the secondary building unit. Topological analysis shows that it has 10‐c uninodal 3D net structure with the Schläfli symbol 3 15 .4 22 .5 8 . The magnetic measurement reveals the tetrahedral coordinated Co II ion. The compound is highly active towards epoxidation in the presence of air and IBA (isobutyraldehyde). It catalyses almost all types of olefinic substrates with equal efficiency. The compound is highly stable thermally (370 °C) and under the reaction conditions as well. After the reaction it can be recovered quite easily and can be used for further reaction without any loss of activity over several cycles. Abstract : A new tetrahedral cobalt phosphonate has been synthesized hydrothermally. It shows an interesting 8‐ring channel structure. It catalyzes olefin epoxidation reaction in presence of O2 /IBA in heterogeneous medium.